SISTEMATIKA NASKAH AKADEMIK SEBAGAI ALAT LEGITIMASI: MENAKAR TEMPAT KONSEP SYURA DALAM PRAKTIK DEMOKRASI KONTEMPORER - Muhammad Hilmi; Muhammad Septian Yoga Pangestu Pangestu; Akhmad Zaki Yamani (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2026)
This study aims to analyze the systematic structure of the Naskah Akademik (Academic Paper) as an instrument of legitimacy in legislative drafting and to examine the position of the concept of shura within contemporary democratic practices. This research employs a normative legal method using statutory, conceptual, and comparative approaches. Legal materials were collected through library research, including legislation, constitutional law literature, democratic theory, and Islamic political thought. The findings reveal that the Academic Paper plays a strategic role as a source of legitimacy by ensuring that legislation is formulated on sound philosophical, juridical, and sociological foundations. Furthermore, the concept of shura embodies the principles of consultation, participation, justice, and accountability, which are compatible with the core values of modern democracy. Nevertheless, both systems derive legitimacy from different foundations, namely popular sovereignty in democracy and Islamic normative principles in shura. The study concludes that shura should not be regarded as incompatible with contemporary democracy but rather as a normative framework capable of strengthening deliberation, public participation, and legitimacy in legislative and public policymaking processes.